Social dominance-subordinate relationship in a flock of Marwari goats - SHINDE, A K; VERMA, D L; SINGH, N P (The Indian Journal of Animal Sciences, 2014)
Social dominance-subordinate behaviour of 20 Marwari goats maintained under group stall-feeding was studied over 10 consecutive days. All the agonistic interactions were pooled to determine dominance value and dominance ranks. From the ranks the tlock was divided into 3 groups of high (DV, 60-90), medium (DV, 30-60) and low (DV, 0-30) ranking goats. High rank goats were first to occupy the trough after feed after and also spend more time in eating feed and fodder than medium and low rank animals. Low rank goa.ts generally preferrcd to consume feed when dominant animals were idling so as to avoid any conflict with them. Dominance was not related to time spent eating dry (r = 0.12) and green (r = 0.12) fodder, height (r = 0.30) and age (r =0.10) of animals. It was, however, positively associated with girth (r = 0.88) and weight (r = 0.90) of the animals and with time spent ruminating (r =0.72), eating concentrate mixture (r = 0.97) and idling (r =0.81). Agonistic interactions were 7.33 times higher (P<0.01) in the feeding than the idling time. During the 1 hr each of feed offer frequency of agonistic behaviour was higher during concentrate (46%) and green (36%) than dry (18%) fodder feeding. High rank animals initiated most but received few, agonistic interactions. Amicable behaviours were altogether absent in the flock. The present study concluded that dominance value of animals was the most important factor influencing the use of feed resources especially when resources are offered under group feeding and also in short supply.